Javier Uriarte, The Desertmakers. Travel, War, and the State in Latin America - Segade, Lara (Prismas - Revista de historia intelectual, 2020)
Javier Uriarte, The Desertmakers. Travel, War, and the State in Latin America, Nueva York, Routledge, 2020, 294 páginas